Geradores higroelétricos para a captação de energia construídos a partir de nanoestrutura de grafite e celulose - Moreira, Kelly Schneider (2020)
Energy–harvesting devices show promising features to enable the operation of low-energy consumption devices, Internet-of-Things (IoT) and wearable electronics. The phenomenon of adsorption of water vapor to produce electric power, hygroelectricity, has been inserted in this context in order to supply the growing electricity demand in daily life. When exposed to variable humidity under shielded or grounded environments, many solids acquire charge as the result of asymmetrical water vapor ions partitioning. HEGs (hygroelectric generators) have been using this phenomenon to generate considerable energy through the moisture diffusion process. In the current literature, we find HEGs that produce an open-circuit voltage of ~0.2V and output power of 0.102 μW. However, most of HEGs show complex construction through expensive technics and slow process to the manufacturing. In this work, we developed an efficient, flexible, not expensive and self-powered device based on the generation of electricity from water sorption on paper coated with nanostructured graphite dispersed in cellulose. In order to increase the partition of water ions, the nanostructured carbon was impregnated with different acid and basic substances. Our best HEG produces an open-circuit voltage of ~0.5 V and an output power of 0.72 μW. Using fifteen disk format pairs (diameter 2 cm) we turn on many white LEDs connected in parallel.